The Role of the Operating Room Manager According to Operating Room Directors: a Qualitative Content Analysis Study - Bernardino Tomei; Caterina Cicala; Alessandro Spano; Antonio Petruzzo (Infermieristica Journal)
Introduction. In healthcare system management, managing operating rooms, which are characterized by a significant production focus and a correspondent high level of complexity, is one of the most current issues, to implement more efficient models, based on a balanced use of resources. Operating Room Management is an emerging model based on Operation Management. Although in literature it is easy to find concepts and tools regarding the Operation Management of surgical items, little is known so far about the roles which should apply these principles. The topic is shown in a few articles, many of these marginally related to it, but none derived from primary studies.